Revolution and class struggle : a reader in marxist politics - Blackburn, Robin (ed.) (Glasgow Fontana/Collins, 1977)
To assemble a reader in Marxist politics is an ambitious, problematic, even presumptuous undertaking. Marxism has transformed the politics of the twentieth century and engaged the talents of many profound revolutionary thinkers. Something like a third of the world's population now lives in countries where there has been a socialist revolution and whose leaders claim that they are inspired by the teachings of Marx and Lenin. In most parts of the world Marxism has been a seminal force within the workers' movement. The ideas of Marx and Lenin have also been drawn upon by revolutionary movements that have won the support of the mass of peasants and of the downtrodden rural poor. Many of those who have fought for the equality and liberation of women, or against national and racial oppression, have been attracted by the Marxist critique of capitalism. Marxism draws on a wide range of sources, from the achievements of classical bourgeois thought to the popular traditions of re bellion in many lands. It has fascinated intellectuals across five continents, yet it has proved capable of transmitting its essential message to millions of toilers, often without any formal education, in every part of the world.
Keywords: Marxist Politics